ORIENT IN POLISH POST-WAR FEATURE FILM. RECONNAISSANCE - Nowakowski, Jacek (Porównania, 2013)
In this paper, I intended to analyse Polish feature films devoted to three central categories: orientalism, postcolonialism and the clash of cultures (civilizations). This article presents the Polish cinema in the following three areas and types. First of all, there are works which show an exotic, oriental space. Secondly, there are films with a hero who is a stranger and an enemy. Finally, in the newest films the protagonist – a new comer from the East – becomes accepted and understood.